2023
DOI: 10.3892/etm.2023.11924
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibitor MG132 enhances the sensitivity of human OSCC cells to cisplatin via a ROS/DNA damage/p53 axis

Abstract: Cis-diamine-dichloroplatinum II (cisplatin, CDDP) is a key chemotherapeutic regimen in the treatment of oral squamous cell carcinoma (OSCC). However, the therapeutic efficacy of cisplatin in OSCC may be hampered by chemoresistance. Therefore, the development of novel combination therapy strategies to overcome the limitations of CDDP is of great importance. The proteasome inhibitor MG132 exhibits anti-cancer properties against various types of cancer. However, our knowledge of its anti-cancer effects in combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The induction of apoptosis was observed simultaneously with the intensification of oxidative stress in HepG2 cells induced through GO/rGO [7]. Similar results were presented by Zheng et al Researchers have shown that MG-132 induces ROS synthesis and at the same time leads to an increase in the level of Bax and p53 proteins and a decrease in the level of Bcl-2 protein in OSCC cells [10]. In our previous study, we indicated that rGO could induce apoptosis through the oxidative stress pathway in ZR-75-1 and MDA-MB-231 cell lines.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The induction of apoptosis was observed simultaneously with the intensification of oxidative stress in HepG2 cells induced through GO/rGO [7]. Similar results were presented by Zheng et al Researchers have shown that MG-132 induces ROS synthesis and at the same time leads to an increase in the level of Bax and p53 proteins and a decrease in the level of Bcl-2 protein in OSCC cells [10]. In our previous study, we indicated that rGO could induce apoptosis through the oxidative stress pathway in ZR-75-1 and MDA-MB-231 cell lines.…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, the proteasome inhibitor MG-132 can effectively inhibit the proteolytic activity of the 26S proteasome complex and induces strong oxidative stress leading to cytotoxicity. It has been shown that the sharp edges of rGO can mechanically damage cell membranes, leading to the release of LDH from cells [10,11]. The ROS cause lipid pre-oxidation, and thus, large amounts of LDH are released into the culture medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In OSCC, different proteasome inhibitors in combination with Cisplatin enhanced apoptosis through dissociation of the E-cadherin/β-catenin complex essential for cell adhesion [ 60 ]. Recently, proteasome inhibitors were shown to sensitize OSCC to Cisplatin through the ROS/DNA damage/p53 axis [ 61 ]. Gimeracil is known to enhance the antitumor effects of 5-FU and improve radiotherapy efficacy by inhibiting DNA repair pathways.…”
Section: New Combinatorial Approaches For Oral Cancer Treatmentmentioning
confidence: 99%